The Dancing Lares and the Serpent in the Garden : Religion at the Roman Street Corner - Flower, Harriet I. (Book collections on Project MUSE., 2017)
The most pervasive gods in ancient Rome had no traditional mythology attached to them, nor was their worship organized by elites. Throughout the Roman world, neighborhood street corners, farm boundaries, and household hearths featured small shrines to the beloved lares, a pair of cheerful little dancing gods. These shrines were maintained primarily by ordinary Romans, and often by slaves and freedmen, to whom the lares cult provided a unique public leadership role. In this comprehensive and richly illustrated book, the first to focus on the lares, Harriet Flower offers a strikingly original account of these gods and a new way of understanding the lived experience of everyday Roman religion. Weaving together a wide range of evidence, Flower sets forth a new interpretation of the much-disputed nature of the lares. She makes the case that they are not spirits of the dead, as many have argued, but rather benevolent protectors--gods of place, especially the household and the neighborhood, and of travel. She examines the rituals honoring the lares, their cult sites, and their iconography, as well as the meaning of the snakes often depicted alongside lares in paintings of gardens. She also looks at Compitalia, a popular midwinter neighborhood festival in honor of the lares, and describes how its politics played a key role in Rome's increasing violence in the 60s and 50s BC, as well as in the efforts of Augustus to reach out to ordinary people living in the city's local neighborhoods.